2021
DOI: 10.3390/fluids6050180
|View full text |Cite
|
Sign up to set email alerts
|

Near Stall Unsteady Flow Responses to Morphing Flap Deflections

Abstract: The unsteady flow characteristics and responses of an NACA 0012 airfoil fitted with a bio-inspired morphing trailing edge flap (TEF) at near-stall angles of attack (AoA) undergoing downward deflections are investigated at a Reynolds number of 0.62 × 106 near stall. An unsteady geometric parametrization and a dynamic meshing scheme are used to drive the morphing motion. The objective is to determine the susceptibility of near-stall flow to a morphing actuation and the viability of rapid downward flap deflection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The laminar trans to turbulent BL is clearly captured as seen in the sudden increase of Cf, and it appear the transition gets closer to the LE the more the main flap is deflected, indicating tha transition has some connections with the LSB. A similar conclusion was drawn in a ence paper [37] when the Stress-Blended Eddy Simulation (SBES) model was used a These predictions may be more realistic compared with the statically morphed wing, as in real-life scenarios, the flap is deployed dynamically which gives rise to unsteady flow phenomena (e.g., vortex formation and convection downstream) that could influence the aerodynamic performance, such as the sudden peaks in drag observed before the final TEF position.…”
Section: Unsteady Rans Of a Dynamically Morphing Tefsupporting
confidence: 57%
See 4 more Smart Citations
“…The laminar trans to turbulent BL is clearly captured as seen in the sudden increase of Cf, and it appear the transition gets closer to the LE the more the main flap is deflected, indicating tha transition has some connections with the LSB. A similar conclusion was drawn in a ence paper [37] when the Stress-Blended Eddy Simulation (SBES) model was used a These predictions may be more realistic compared with the statically morphed wing, as in real-life scenarios, the flap is deployed dynamically which gives rise to unsteady flow phenomena (e.g., vortex formation and convection downstream) that could influence the aerodynamic performance, such as the sudden peaks in drag observed before the final TEF position.…”
Section: Unsteady Rans Of a Dynamically Morphing Tefsupporting
confidence: 57%
“…Moreover, the intermittency k-ω SST model is used for turbulence closure, and a second order upwind scheme is utilized for the momentum and turbulence equations discretization. The intermittency k-ω SST has been chosen as it offers a good balance between the accuracy and computational cost, it has been shown that it is perfectly adequate for this type of turbulent separated flow [47], offering better predictions than the Spalart-Allmaras model [48], but at only a fraction of the cost compared to higher fidelity turbulence models, such as the hybrid SBES which has been used in previous published 2D work [37].…”
Section: Steady Ransmentioning
confidence: 99%
See 3 more Smart Citations